Analyse des causes des impayés dans le processus d'octroi de crédit dans les institutions de microfinance au Cameroun : cas de la Bourse d'Epargne et de Crédit (BEC) - Voukeng, Ghislain-Blaise (Université de Liège, 2016)
Microfinance institutions are specialized in the financing of economic activities of small sizes. They have a social role to target many excluded from the traditional financial system, including poor households, sole proprietorships, small and medium enterprises and mutual aid associations by offering to them suitable financial services (Kobou et al. 2009). In doing so, they are perceived by the vast majority of public opinion internationally as a useful lever for poverty reduction. They must nevertheless obtain sufficient economic and financial results to ensure their viability and sustainability. But in recent decades, there is a certain fragility of MFIs with cases of cascading bankruptcy in Cameroon, where one of the major causes of this bankruptcy remains the unpaid. This study examines the causes of the unpaid loan in the microcredit process in second category of microfinance institutions in Cameroon through the specific case of the "Bourse d’Epargne et de Credit" (BEC). To do this, a multi-variables analysis based on logistic regression method was performed on 195 individuals who have benefited the credit based on six factors, including the sex of the applicant (male or female), the socio professional category of applicant (trader, employee, and very small business-man), the credit period, the number of times an individual has benefited a credit, interest expenses borne by the applicant and the time to study and reply one credit demand. After analysis and discussion, it emerges that: the very small business-man, credit duration, the number of times an individual has benefited the loan; the interest charges borne by the customer are risk factors that increase the level of unpaid with a significant level of 5%. Other factors of the professional category (trader and employee); the credit applicant customer's gender (male or female) and the time to study and reply to a credit demand are factors that have low risk for unpaid. These factors are considered as protective factors of unpaid, also at the significant level of 5%. In addition, it also shows that certain portion of the target where credit is granted is unsuited to the context of the institution's objectives; there is a managerial problem in the structure in question.
Keywords: Credit; Microfinance institution; Risk; Sustainability; Unpaid loan